71.4k views
4 votes
Evaluate the expression 2n(n-1), when n =
= 3
A 11
B 12
C 17
D 18

User Zyo
by
5.8k points

1 Answer

2 votes

Answer:

The value of the expression is 12B

Explanation:

Let us solve the question

∵ The expression is 2n(n - 1)

→ Simplify it at first by multiply 2n by the bracket (n - 1)

∵ 2n(n - 1) = 2n(n) - 2n(1)

2n(n - 1) = 2n² - 2n

n = 3

→ Substitute n by 3 in the expression to find its value

∴ 2n² - 2n = 2(3)² - 2(3)

∴ 2n² - 2n = 2(9) - 6

∴ 2n² - 2n = 18 - 6

2n² - 2n = 12 ⇒ at n = 3

The value of the expression is 12

User Nicholas Kong
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.